The Role of the Audit Committee On the Performance of Indonesian State-Owned Enterprises (BUMN) Registered on the Indonesia Stock Exchange - Mochamad Muslih (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
It has never been thoroughly investigated whether the existence of the Audit Committee on the SOE board of commissioners is truly as beneficial as expected. Based on research that has been done, there is still a diversity of opinions regarding the effect of audit committee characteristics on company performance. The purpose of this study is to study whether audit committee size and number of audit committee meetings affect company performance. The grand theory of this research is agency theory or agency theory and corporate governance. This research uses quantitative research methods. Data processing is performed using eviews 9. The unit of analysis is the company. The sample is 20 (twenty) SOEs registered on the Indonesia Stock Exchange from 2013 to 2018. The sample must also be BUMN that has a complete Audit Committee report. The results showed that the number of chairpersons and members of the audit committee had a positive effect on company performance, the number of audit committee meetings had no significant effect on company performance, and the size of the company had a significant negative effect on company performance.